Advances in Spiky Antibacterial Materials: From Bioinspired Design to Application - Zijun Zhang; Limei Qian; Nan Zhang; Xinyue Wang; Yunshen Fu; Guanbin Gao; Taolei Sun (Small Structures)
Bacterial infections, particularly those caused by drug‐resistant bacteria, pose a significant threat to human life and health safety. Despite the preparation and application of numerous antibacterial and disinfection materials, addressing their low efficiency and the emergence of drug resistance remains an urgent concern. Inspired by natural spike antibacterial structures such as those found on cicada wings, extensive research has been conducted on biomimetic antibacterial materials with spiky structures. This review provides an overview of the natural spike antibacterial structure and mechanism, introduces surface coatings and micro/nanoparticle materials featuring spike structures inspired by nature, explores microneedle arrays based on spike antibacterial properties, and showcases applications of these innovative antibacterial materials. Finally, potential avenues for optimization and future development directions for antibacterial materials with spike structures are discussed.